Desarrollo y Medio Ambiente en España. Estudio de caso: Los problemas medioambientales y - Sotelo Navalpotro, José Antonio; García Quiroga, Fernando; Abad Soria, Jesús; SOTELO PÉREZ, María (Observatorio Medioambiental, 2010)
The metabolic index of environmental sustainability has become well known in recent years. Especially the Ecological Footprint index, since it has proven to be a very useful tool for comparing the geographical area occupied by a population with the natural area that is necessary to sustain that population indefinitely. Recent studies indicate that in general, in developed countries the ecological location of human settlements does not coincide with their geographic location. This article analyzes the Ecological Footprint calculation at different scales, within the Autonomous District of Castilla and Leon.
Keywords: Development; Sustainability; Ecological footprint; Biodiversity